Intellectual Capital And Financial Performance: The Case Of Plantation Companies In Indonesia - et. al., Andina Nur Fathonah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Intellectual Capital in Indonesia began to develop from the emergence of PSAK No. 19 (revised 2000) regarding intangible assets. This indirectly supports the company to disclose information about IC in detail by itself will create company value. IC can support competitiveness in the market so that an entity's financial performance can be even better. Researchers take the object of research into plantation companies, it is assumed that plantation companies need large resources in managing natural resources so they must be serious in handling them.